Manual de sequências didáticas: uma abordagem investigativa, dinâmica e contextualizada do ensino de biologia - Teixeira Neto, Carlos Santos Pinon (2020)
Amid great technological evolution, a big increase in information access and a fast flux of data, a low interest by the students about Natural Sciences is noticed. Searching improvements in methodological proposals, it is proposed in this article to develop of a didactic sequences manual, aiming at a better learning of Biology contents in high school in the Young and Adults Education modality, containing five didactic sequences, that approach, the themes of Biochemistry, Cell Biology, Histology and Embryology, using active methodologies, stimulating the student's to the leading role and exploring the investigative bias. The activities were realized in the school “Escola Estadual de Ensino Fundamental e Médio Áudio Comunicação” from João Pessoa, in two classes from the fifth cicle, with 15 students in class “A” and tem stundents in class “B” class (control), in the Young and Adults Education modality. The methodology followed the qualitative aspect, inside the research-action model and quantitative aspect, where the effiency evaluation of the proposal was made through analyze of pre and post tests, among other activities realized inside the classroom. In the activities, diversified didactal ressources were used such as experimental classes, movies exibition, analyzes of labels and leaflets and scientific dissemination texts. The data that were obtained through the tests, along with the classroom observation confirmed the dificulties that the students demonstrated related to biology contends. The prevalence of a tradicional model that prestiges the teaching by memorizing, makes it harder to reach a deeper learning and the contextualization of the worked themes, making the presencial classes uninteresting and pointless for the students. Starting from the application of the classes proposed in the manual, the students came across with a new reality, where they were stimulated to look for the construction of knowledge through an investigative process, taking on the lead role of their actions. It was possible to watch a behavior changing by the students, internalizing this new culture, taking to positive results in the sense of learning of the worked content aspects, but also in the improvement of de argumentative ability, in the capacity of working autonomously, and comprehending and contextualizing the themes with their daily routine without mention their knowledge sistematization. The results indicate that, in the goups A and B (control), the dificulties had persisted inherent to the expression of ideas and concepts in the writen form. When compared to the abtained average in the pre and post test, it was verified that, in group A, where the manual metodologies were applied, there was an increase of 118% on the grades, reaching an average of 6,5 points, while in group B, the increase was of 50%, reaching an average of 4,4 points. With this, we can conclude that the proposal was efficient and supplied the proposed objectives, in the meaning of approaching the cientific knowledge, giving practical meaning to it, and providing an improvement with the students learning, which started to assume the lead role in the process, showing the relevance of the metodological path to the construction and re-meaning of knowledge, respecting and giving value to their histories and personal knowledges.